A performance of 2 dimensional ultrasonic vibration assisted milling in cutting force reduction, on aluminium AL6061 - Ibrahim, Rasidi; Rafai, Noor Hakim; Abd. Rahim, Erween; Kai, Cheng; Hui, Ding (Asian Research Publishing Network (ARPN), 2016)
This paper were investigate a performance of 2 Dimensional Ultrasonic Vibration assisted Milling (UVAM) toward Aluminium Al 6061. The focus is to find the performance of reduction of cutting force compared to the conventional machining in the industries shop floor. Due to the major effect of cutting force of production in industries, the excessive cutting force problem must be investigated deeply as it will cause shortens tool life and reduces the production rate. A scientific approach has been found in order to reduce the cutting force during machining which is integrating the ultrasonic concept into workpiece. The modelling of vibration cutting ratio has been simulated to find the time force contact and non-contact. Thus, less cutting force could be found. The ultrasonic vibration platform that generated by XY25XS from Cedrat Technologies is travelled in X direction as a feed movement. Thus, the X and Y axis vibration actuate along the workpiece for the machining process. The performance of UVAM in cutting force reduction found the superior benefits of UVAM is come from the alternating cycle’s between tool and workpiece. The comparison between UVAM and conventional machining in reduction of cutting force is 32%. The potential of the UVAM tool wear and tool life will be discussed deeply in finding and next in the conclusion section.